Preparation of a Green Photocatalyst by Immobilization of Synthesized ZnO Nanosheets on Scallop Shell for Degradation of an Azo Dye - Shirzad-Siboni, Mehdi; Khataee, Alireza; Vahid, Behrouz; W. Joo, Sang; Fallah, Sevda (Current Nanoscience, 2014)
Photocatalysis of C.I. Acid Red 14 (AR14) by immobilized ZnO nanosheets on scallop shell was investigated. The mean crystallite size of the ZnO nanosheets on scallop shell sample was about 15 nm. Degradation efficiency of AR14 by immobilized ZnO is more efficient than suspension form in identical conditions. Effect of operational parameters including nanocatalyst dosage, pH and initial dye concentration on the UV/ZnO-scallop process was studied. Kinetic of the photocatalytic process was explained in terms of the Langmuir–Hinshelwood model. The values of the kinetic rate and the Langmuir adsorption constants were determined as 0.104 1/(mg/L) and 0.413 (mg/L)/min, respectively. The prepared photocatalyst demonstrated the proper photocatalytic activity even after five successive cycles.
Keywords: Nanocatalyst